The value of using the autocad program in the works of machine-building drawings for building fastening parts - Mamurova Dilfuza Islamovna (Proceedings of The ICECRS, 2019)
This paper makes analyses according to XXI century, not for nothing called the century of information technology. With the development of modern technologies, information and communication technologies are widely used in all educational institutions. The use of information and communication technologies in the lessons and classes of mechanical engineering, as well as the problems of computerization, required several observations and solutions. In this way, it concludes, information computer technologies you can clearly show and explain the possibilities of computer technologies, which allows you to master the topic well.